К вопросу о методологии сравнительного исследования геноцида армян и геноцида евреев - Сафрастян, Рубен («Զանգակ - 97»)
The paper deals with the methodology of Genocide, carried out on the 1915 Annenian Genocide and Jewish Holocaust. The author concluded that the true picture of both could be reached if one would carry a thorough analyses of the Ottoman Empire and Germany, focusing on the typology of these states.
Keywords: История; Геноцид